Naluri Pendidikan Karakter Meneladani Kisah Al-Hakim - Santi Fauziah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
In life, the main goal of a human being is to become a complete human being, who can be self-sufficient and socialize well. Have self-awareness to live a better and peaceful life. It is through education that humans are trained and accustomed to achieve complete goals. Character education is not a process of memorizing exam question material or techniques for answering exam questions. But character education is an habituation. The habit of doing good, habituation of respecting others, habituation of being honest, habituation not to be lazy, habituation of respecting time, and so on. All of that must be trained seriously and proportionately in order to achieve the ideal form and strength. Character education is a very important stepstrategic in rebuilding the national identity and mobilizing the formation of a new Indonesian society. The approach in this research is literature study. As we all know Luqman Al Hakim is a wise person who is a role model for many human beings including writers. This time, a literature study on how the character education instincts of al-judge will be discussed by the author. How is the series of moral decisions (Moral Choice) which are followed up with real action by Al Hakim, in full will be explained by the author in the following discussion